Biofloc technology mitigates heavy metal stress and improves growth, health, and microbial balance of Nile tilapia cultivated in contaminated lake water - Walied M. Fayed; Ghada R. Sallam; Tarek A. Srour; Adel H. Elsenbawi; Omneya Ibrahim; Ahmed E. Sallam; Akram Ismael Shehata; Mohammed F. El Basuini (Aquaculture International, 2026)

Strategic application of biofloc technology for optimizing physiological homeostasis and reproductive efficiency in red tilapia (Oreochromis spp.) broodstock under long-term rearing conditions - Ghada R. Sallam; Mohammed F. El Basuini; Mayada Alhoshy; Mohamed A. Al-Absawey; Yusuf Jibril Habib; Ashraf I. G. Elhetawy; Islam I. Teiba; Mohamed M. Abdel-Rahim; Basem S. Abdelaty; Ahmad A. Kashuit; Walied M. Fayed; Hafez A. H. Mabrouk; et al. (Aquaculture International, 2025)
This study evaluated the effects of biofloc technology (BFT) on male and female red tilapia ( Oreochromis spp.) broodstock over a long-term rearing period, focusing on the pre-spawning and spawning phases. A total of 1000 mixed-sex acclimated fingerlings (36.88 ± 3.44 g) to 18 parts per thousand salinity over 15 days were assigned to either BFT or clear water control tanks. During the pre-spawning phase, BFT enhanced water quality, improved growth and feed efficiency, and significantly promoted reproductive performance and metabolic regulation in broodstock. During the spawning phase, broodstock were distributed into four treatments: (1) control (C–C), reared in clear water during pre-spawning and spawning, respectively; (2) BF-BF, reared in BFT during both phases; (3) C-BF, reared in clear water pre-spawning and BFT during spawning; and (4) BF-C, reared in BFT pre-spawning and clear water during spawning. Strategic BFT application significantly reduced time to first spawning and increased fecundity, egg quality, hatchability, and total fry production. Water quality remained superior, with lower total ammonia–nitrogen, NO 2 -N, and NH 3 , and higher NO 3 -N and phytoplankton activity. BFT enhanced nutrient assimilation and reduced pathogenic bacteria, though prolonged exposure impaired physiological balance, reproduction, and hormonal regulation. To maximize benefits while minimizing risks, a phased BFT strategy is recommended. Specifically, BFT should be applied during the pre-spawning phase to enhance broodstock conditioning, reproductive development, and immune function, followed by a transition to clear water during spawning to prevent physiological stress and hormonal imbalances. This approach ensures optimal reproductive outcomes while maintaining long-term broodstock health. Future research should focus on refining BFT application based on species, size, gender, and specific nutritional requirements to further optimize sustainable aquaculture production.

Fertilization sources fallout: Unveiling the impacts on growth, metal accumulation, and physiological responses in Nile Tilapia, Oreochromis niloticus - Ghada R. Sallam; Walied M. Fayed; Mohamed Alaa; Mohamed Fayek; Islam I. Teiba; Mayada Alhoshy; Eslam Tefal; Mohammed F. El Basuini; Akram Ismael Shehata (Aquaculture, 2025)

Salinity-dependent effects of integrated biofloc technology on reproductive performance, biological responses, and offspring quality in red tilapia aquaculture - Ghada R. Sallam; Mohammed F. El Basuini; Amal F. Fahmy; Mohamed A. Al-Absawey; Yusuf Jibril Habib; Rahma Ahmed Mustafa; Walied M. Fayed; Abdel-Fattah M. El-Sayed; Akram Ismael Shehata (Aquaculture International, 2025)
The study aims to evaluate the reproductive performance, serum biochemical indices, growth, antioxidant capacity, and immune response of Florida Red Tilapia ( Oreochromis sp.) progeny reared at different salinity levels within biofloc technology (BFT) systems, focusing on egg production, fertilization rates, tolerance to oxidative stress, and offspring performance. Broodstock reared in biofloc systems (BF) were compared to those in clear water (Without biofloc, WBF) across three salinity levels (18, 28, and 36‰) over a 7-month period. The study also assessed the tolerance of fry reared in biofloc systems to direct transfer to high salinity (36‰) without prior acclimatization. A total of 216 females (initial body weight: 182 ± 1.8 g) and 72 males (initial body weight: 201 ± 0.88 g) were randomly assigned to 18 concrete tanks (2 × 6 × 1 m) to investigate the effects of BFT on spawning performance and larval survival under high-salinity conditions. The findings indicated that appropriate salinity (18‰) in BFT systems positively affected reproductive efficiency, enhanced immunological parameters, and improved growth performance, but elevated salinity levels (36‰) led to reduced reproductive success and hindered growth performance. Florida red tilapia thrive in water quality conditions that are within acceptable limits. High salinity environments led to increased dissolved oxygen but reduced pH, especially in BFT ponds. BFT improved reproductive performance, reduced spawning time, and increased egg production. It also improved hatchability, larval quality, and yolk sac absorption. The BFT broodstock showed higher levels of key proteins (total protein, albumin, and globulin) and improved immune parameters, which helped counteract the negative effects of elevated salinity and enhanced their overall health and stress tolerance. In high-salinity environments, offspring in BFT systems showed higher survival rates and growth rates. In conclusion, BFT improves the reproductive performance, growth, and immune response of Florida red tilapia under high salinity. It enhances egg production, hatchability, and larval survival, while also improving water quality and immune function, making it a sustainable solution for tilapia aquaculture in saline environments.

Integrated biofloc technology in red tilapia aquaculture: Salinity-dependent effects on water quality, parental stock physiology, reproduction, and immune responses - Ghada R. Sallam; Akram Ismael Shehata; Mohammed F. El Basuini; Yusuf Jibril Habib; Shimaa Henish; Afaf N. Abdel Rahman; Youssef M. Hassan; Walied M. Fayed; Abdel-Fattah M. El-Sayed; Hadir A. Aly (Aquaculture International, 2024)
The study examines the impact of integrated biofloc technology (BFT), different salinity levels, and their combined effects over 90 days on various physiological parameters. The investigation includes growth performance and feed utilization, water quality, the chemical composition of biofloc and fish, digestive enzymes, reproductive performance, stress and biochemical indicators, and antioxidant-immune responses in red tilapia ( Oreochromis spp .) broodstock. The fish were initially weighed (males: n = 270; 104 ± 0.96 g; females: n = 270; 93.2 ± 0.66 g) and subsequently divided into 12 treatment groups (6 for males and 6 for females) spread across 36 separate tanks (3 tanks per treatment; 45 fish per treatment; 15 fish/tank). The treatments involved three salinity levels (18, 28, and 36 ppt) in both clear water (CW) and BFT systems. The outcomes demonstrated that fish in the 36 ppt salinity with BFT treatment demonstrated significant improvements ( P P P

Phyto-additive fueling fertility: Nanocurcumin enhances red tilapia foundation stock breeding in saline waters - Ghada R. Sallam; Walied M. Fayed; Mazen A. Elsawaf; Hafez A.H. Mabrouk; Mohamed A. Al-Absawey; Shimaa Henish; Mohammed F. El Basuini; Akram Ismael Shehata (Aquaculture, 2024)